Evaluation of resilience modulus of polymer-modified asphalt mixture using gypsum filler - Dwi Esti Intari; Rindu Twidi Bethary (Jurnal Teknika, 2021)
Road infrastructure plays an important role as one of the driving wheels of economic growth and development so that during its service life, it can provide good comfort and safety with quality that must be met. The selection and change of materials used are measures to preserve the pavement construction quality. The utilization and renewal of waste in the road construction sector have become important. One of the waste materials in road construction developed is gypsum powder because the lime (CaO) content is quite high. Resilience modulus is one of the fundamental parameters used in determining the quality of the material used and measuring the stiffness of the asphalt concrete mixture. This study aims to determine the mechanical properties or the resilience modulus of the HRS-WC lataston asphalt mixture using polymer modified asphalt with gypsum powder as a filler. Based on the results obtained, it is known that the addition of gypsum filler into the lataston asphalt mixture can reduce the value of the resilience modulus so that the stiffness in the mixture is reduced and can make the mixture more resistant to repeated loads. Infrastruktur jalan memegang peranan penting sebagai salah satu roda penggerak pertumbuhan ekonomi dan pembangunan sehingga selama umur layan dapat memberikan kenyamanan dan keamanan yang baik dengan kualitas yang harus dapat terpenuhi Salah satu upaya untuk menjaga kualitas struktur perkerasan adalah dengan pemilihan dan modifikasi material yang digunakan. Pemanfaatan dan pembaharuan limbah dalam sektor konstruksi jalan menjadi isu yang penting salah satu material limbah dalam konstruksi jalan yang telah dikembangkan adalah bubuk gypsum, karena kandungan kapur (CaO) yang cukup tinggi. Modulus resilien merupakan salah satu parameter fundamental yang digunakan dalam menentukkan kualitas material yang digunakan juga ukuran kekakuan campuran beton aspal. Penelitian ini bertujuan untuk mengetahui karakteristik sifat mekanis atau atau modulus resilien pada campuran aspal lataston HRS-WC yang menggunakan aspal modifikasi polimer dengan bubuk gypsum sebagai filler. Berdasarkan hasil yang diperoleh diketahui bahwa dengan adanya penambahan filler gypsum ke dalam campuran beraspal lataston dapat menurunkan nilai modulus resiliennya sehingga kekakuan dalam campuran berkurang dan dapat membuat campuran tersebut lebih tahan terhadap beban berulang.